(untitled) (American Journal of Technology and Applied Sciences, 2025)
In cotton ginning enterprises, it is of great importance to dry cotton before cleaning it. Drying cotton is carried out using thermal energy. The main disadvantage of modern drying drums operating in enterprises is the fact that the temperature rises or falls, which, as a result, causes a violation of the quality of the product. If the raw materials of cotton are not well dried in the later stages, that is, the processes of cleaning, ginning have a negative effect on the productivity of work and the quality of raw materials. If the drying agent temperature is high during the drying process, the fiber quality during the Jinning process and lead to damage to the seed. With this in mind, based on the results of this scientific research, it will be advisable to choose the law of adjusting the Scada system, which controls the temperature in the drying drum.